A Qualification-Based Analysis of Critical Success Factors Affecting Contractor Performance in Indonesia's Public Construction Tenders - Palembangan, Memed Timang; Latief, Rusdi Usman; Arifuddin, Rosmariani; Abdurrahman, M. Asad (Engineering, Technology & Applied Science Research, 2026)
This study examines the Critical Success Factors (CSFs) influencing contractor performance in winning public construction tenders under Indonesia's Ministry of Public Works using a qualification-based comparative approach. A quantitative design was employed, with data collected from 597 contractors (161 small, 187 medium, and 249 large firms). Separate Structural Equation Modeling–Partial Least Squares (SEM-PLS) estimations were conducted for each contractor category, followed by a cross-group comparative analysis to identify scale-sensitive differences in CSF significance. The results reveal that Competitive Pricing and Equipment Resources consistently serve as significant determinants of tender success across all contractor classifications, confirming their universal importance within Indonesia's cost-driven and compliance-oriented procurement system. However, the influence of other CSFs varies by organizational scale. Small contractors are primarily influenced by Technology and Innovation and Regulatory Understanding; medium contractors by Company Qualification, Human Resources, and Document Quality; and large contractors by integrated resource management and regulatory risk control. This study is the first to apply a qualification-based comparative SEM-PLS framework, demonstrating that organizational scale moderates CSF relevance in public construction tendering. The findings challenge the prevailing one-size-fits-all perspective and provide scale-sensitive theoretical and practical implications for contractor strategy and public procurement policy in developing-country contexts.